Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 3 - Section 3.4 - Exponential and Logarithmic Equations - Exercise Set - Page 488: 21



Work Step by Step

RECALL: (i) If $a^M=a^N$, then $M=N.$ (ii) $\dfrac{1}{a^m} = a^{-m}.$ Use rule (ii) above to obtain $e^{x+1} = e^{-1}.$ Use rule (i) to obtain $x+1 = -1.$ Solve the equation: $x+1-1 = -1-1 \\x=-2.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.